Wildlife in the Digital Anthropocene: examining human-animal relations through surveillance technologies - Von Essen, E; Turnbull, JJ; Searle, A; Jørgensen, FA; Hofmeester, TR; Van Der Wal, R (SAGE Publications, 2021)
Digital surveillance technologies enable a range of publics to observe the private lives of wild animals. Publics can now encounter wildlife from their smartphones, home computers, and other digital devices. These technologies generate public-wildlife relations that produce digital intimacy, but also summon wildlife into relations of care, commodification, and control. Via three case studies, this paper examines the biopolitical implications of such technologically mediated human-animal relations, which are becoming increasingly common and complex in the Digital Anthropocene. Each of our case studies involves a different biopolitical rationale deployed by a scientific-managerial regime: (1) clampdown (wild boar); (2) care (golden eagle); and (3) control (moose). Each of these modalities of biopower, however, is entangled with the other, inaugurating complex relations between publics, scientists, and wildlife. We show how digital technologies can predetermine certain representations of wildlife by encouraging particular gazes, which can have negative repercussions for public-wildlife relations in both digital and offline spaces. However, there remains work to be done to understand the positive public-wildlife relations inaugurated by digital mediation. Here, departing from much extant literature on digital human-animal relations, we highlight some of these positive potentials, notably: voice, immediacy, and agency.